2002
DOI: 10.1103/physreve.65.031914
|View full text |Cite
|
Sign up to set email alerts
|

Initial state randomness improves sequence learning in a model hippocampal network

Abstract: Randomness can be a useful component of computation. Using a computationally minimal, but still biologically based model of the hippocampus, we evaluate the effects of initial state randomization on learning a cognitive problem that requires this brain structure. Greater randomness of initial states leads to more robust performance in simulations of the cognitive task called transverse patterning, a context-dependent discrimination task that we code as a sequence prediction problem. At the conclusion of traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The weight of a synapse from pyramidal cell i to the feedback interneuron are updated as Randomization of the initial state, Z(0), (see Shon et al 2002) is part of model fα. On each trial, both training and testing, a · n neurons are activated by a uniform random process.…”
Section: Models and Methodsmentioning
confidence: 99%
“…The weight of a synapse from pyramidal cell i to the feedback interneuron are updated as Randomization of the initial state, Z(0), (see Shon et al 2002) is part of model fα. On each trial, both training and testing, a · n neurons are activated by a uniform random process.…”
Section: Models and Methodsmentioning
confidence: 99%
“…In that model, free recall proceeded by using hippocampal context as a probe for cortical items; in item recognition cortical items were used as a probe to try and recover hippocampal context (see also Dennis & Humphreys, 2001;Schwartz, Howard, Jing, & Kahana, in press). Similarly, a model of sequence learning that has been applied to a number of learning tasks (Levy, 1996;Shon, Wu, Sullivan, & Levy, 2002;Wu & Levy, 1998 argues that one function of the hippocampus is to support local context states that depend on the item presented and the temporal context it is presented in. These local context neurons bridge across temporally proximate item presentations, providing a possible explanation of the temporally-defined associations described by TCM (Kahana, 1996;Howard & Kahana, 1999).…”
Section: A Mapping Hypothesis Onto the Mtlmentioning
confidence: 99%
“…If a neuron fires on only one timestep, then that neuron's context length is one. Previous studies [3,6] have demonstrated a correlation between the mean context length of all of the neurons in the network and learning performance.…”
Section: The Modelmentioning
confidence: 94%